Respostas
respondido por:
0
3 (x-2) = x+6+1 --> multiplica o 3 com (x-2)
3x-6 = x+6+1
3x-x = 6+1+6 --> coloca letras de um lado e números do outro (invertendo o
2x= 13 sinal ao mudar o lado)
x= 13÷2
x= 6,5
3x-6 = x+6+1
3x-x = 6+1+6 --> coloca letras de um lado e números do outro (invertendo o
2x= 13 sinal ao mudar o lado)
x= 13÷2
x= 6,5
respondido por:
0
3(x-2)=x+6x+1
3x-6=x+6x+1
3x-x-6x=1+6
-4x=7
x=7/-4
o valor do x é -7/4
3x-6=x+6x+1
3x-x-6x=1+6
-4x=7
x=7/-4
o valor do x é -7/4
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás